2013
DOI: 10.1158/1078-0432.ccr-13-0884
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA and AKT1 Mutations Have Distinct Effects on Sensitivity to Targeted Pathway Inhibitors in an Isogenic Luminal Breast Cancer Model System

Abstract: Purpose Activating mutations in the phosphoinositide-3-kinase (PI3K)/AKT/mTOR pathway are present in the majority of breast cancers and therefore are a major focus of drug development and clinical trials. Pathway mutations have been proposed as predictive biomarkers for efficacy of PI3K-targeted therapies. However, the precise contribution of distinct PI3K pathway mutations to drug sensitivity is unknown. Experimental Design We describe the creation of a physiologic human luminal breast cancer cell line mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 33 publications
7
89
2
1
Order By: Relevance
“…AKT1 activation in MCF-7 cells is dependent on PIK3CA-E545K mutation (28) and results presented in Figs. 1 and 2 suggest preferential effect of this PIK3CA mutation on AKT1 activation.…”
Section: Discussionmentioning
confidence: 81%
“…AKT1 activation in MCF-7 cells is dependent on PIK3CA-E545K mutation (28) and results presented in Figs. 1 and 2 suggest preferential effect of this PIK3CA mutation on AKT1 activation.…”
Section: Discussionmentioning
confidence: 81%
“…Whatever the explanation, AKT1 E17K clearly has the potential to confer two properties of oncogenic transformation on recipient breast epithelial cells: the ability to grow anchorage independently in semisolid medium and the ability to form mammary lesions in immunodeficient rodents. Moreover, recent data have shown that knock-in of AKT1 E17K into isogenic MCF-7 cells that have previously been depleted of their endogenous PIK3CA E545K mutation restored proliferation and tumor growth (16).…”
Section: Discussionmentioning
confidence: 99%
“…The E17K mutation has been shown to constitutively activate AKT1 by increased localization to the plasma membrane, where it stimulates downstream signaling and can transform Rat1 fibroblasts and induce leukemia in mice (15). Although knock-in of AKT1 E17K into isogenic MCF-7 breast cancer cells depleted of endogenous PIK3CA E545K restored proliferation in vitro and tumor growth in vivo (16), knock-in of E17K into the AKT1 gene of nontransformed MCF10A mammary epithelial cells had minimal phenotypic consequences and did not recapitulate the transforming properties induced by somatic cell knock in of PIK3CA hotspot mutations (17). In addition, the consequences of directly inhibiting this target in endogenous models of breast and urinary bladder cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both MCF7-corrected and MCF7-corrected + V777L cells had dramatically reduced AKT phosphorylation. Although it has been shown that the absence of PIK3CA mutations in MCF7 cells lowers activation of the PI3 kinase/AKT pathway (19), it was unexpected that isolated activation of HER2 signaling via the V777L mutation MCF-10A Targeted WT 1 Targeted WT 2 Targeted WT 3 G309A S310F L755S I767M V777L Y835F did not lead to any discernible increase in AKT phosphorylation. This result, along with the concurrent increases in ERK phosphorylation, again suggests that V777L HER2 preferentially activates the MAP kinase signaling pathway rather than the PI3 kinase/AKT signaling pathway.…”
Section: Her2 V777l Mutation Increases Her2 Signaling Pathway Activatmentioning
confidence: 99%
“…Numerous studies have implicated PIK3CA mutations in transformation and activation of the PI3 kinase/AKT pathway (17,20). To test this hypothesis, we used genome editing to introduce the HER2 V777L mutation into MCF7 cells that had previously undergone gene targeting to restore the PIK3CA alleles to wild type (referred to as MCF7 corrected) (19). The resulting cells have three wildtype copies of PIK3CA and a heterozygous HER2 V777L mutation (referred to as MCF7 corrected + V777L).…”
Section: Her2 V777l Mutation Increases Her2 Signaling Pathway Activatmentioning
confidence: 99%